Diallel analysis of seven quantitative traits in deshi jute (Corchorus capsularis L.) - Khatun, Rahima; Sarker, RH; Sobhan, MA (Bangladesh Journal of Botany, 2011)
Genetic constitution of yield and its associated traits of Corchorus capsularis L. was investigated using a 10 × 10 full diallel cross experiment. Additive gene action system with partial dominance was predominat for plant height, technical height, base diameter and number of nodes in F1. Non-allellic interaction was involved in the inheritance of bark weight and stick weight in F2. The Vr - Wr graph for bark weight and fibre weight of F1 and F2 showed an additive genetic system with dominance effect. The parents Acc. 4087 and var. A-38 possessed maximum number of dominant alleles for most of the characters. Acc.1833 possessed an excess of recessive genes for all the characters. Key words: Diallel analysis; Inheritance; Dominance effect; Corchorus capsularis DOI: 10.3329/bjb.v39i2.7299 Bangladesh J. Bot. 39(2): 137-141, 2010 (December)